1996
DOI: 10.1111/j.1469-8137.1996.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Festuca arundinacea to fungal endophyte infection

Abstract: SUMMARYEnhanced growth rates of several grass species infected by fungal endophytes are known, hut the underlying changes in plant physiology are not. Carbon exchange rates (CER) and leaf conductances {g) of 13 genotypes of tall fescue {Festuca arundinacea Schreb. var. KY 31) infected by the fungal endophyte Acremonimn coenophialum Morgan-Jones and Gams were measured at ambient conditions. Endophyte-free ramets of the same genotypes were also measured. Correlations were calculated hetween environmental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 31 publications
5
84
0
Order By: Relevance
“…Our study indirectly shows that herbivory is less important in explaining this potential mutualism than previously thought and that endophyte-induced drought tolerance may be more crucial. This and other studies show a narrow ecological range where endophytes are markedly mutualistic (Cheplick et al 1989;West 1994;Marks and Clay 1996). For example, it is known that C 3 grasses are less successful than C 4 in more xeric conditions (Barnes et al 1983;Archer 1984).…”
Section: Ecology Of F Arundinacea and Cool Season Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study indirectly shows that herbivory is less important in explaining this potential mutualism than previously thought and that endophyte-induced drought tolerance may be more crucial. This and other studies show a narrow ecological range where endophytes are markedly mutualistic (Cheplick et al 1989;West 1994;Marks and Clay 1996). For example, it is known that C 3 grasses are less successful than C 4 in more xeric conditions (Barnes et al 1983;Archer 1984).…”
Section: Ecology Of F Arundinacea and Cool Season Grassesmentioning
confidence: 99%
“…Earlier and greater leaf rolling and better long-term survival under water stress are related to endophyte-infected versus uninfected F. arundinacea (Arachevaleta et al 1989). At high leaf temperatures, photosynthetic rates of up to 25% higher are found in infected plants (Marks and Clay 1996). Under water stress, infection-affected stomatal activity leads to reduced water loss from transpiration (Malinowski et al 1997) as well as maintained turgor pressure (Bacon and Hill 1996).…”
Section: Drought Tolerance Of Tall Fescue and Diversitymentioning
confidence: 99%
“…Studies of photosynthetic processes in grasses infected with foliar endophytes are not conclusive and rates of net photosynthesis can be increased (Belesky et al, 1987;Amalric et al, 1999), unchanged or decreased (Spiering et al, 2006), depending on the growth phase of the host plants, nutrient status, and environmental conditions. Marks and Clay (1996) demonstrated an endophyte by temperature interaction, and Newman et al (2003) found an endophyte by N interaction on photosynthetic rates. Effects of endophyte infection on growth also strongly depend on host genotype, resource availability, and environmental stress (Belesky et al, 1989;Malinowski and Belesky, 2006;Morse et al, 2002;Cheplick and Cho, 2003;Hesse et al, 2003;Zabalgogeazcoa et al, 2006;Cheplick, 2007).…”
Section: Effects Of Endophyte Infectionmentioning
confidence: 99%
“…Phenol and its compound are distributed in many plants, phenolic compound are used for the treatment of many disorder and also due to its toxic action prevent the growth of many pathogens [14]. Flavonoids, sterol, and saponins are essential secondary chemical present in above 85 families, due to their multipurpose and specific chemistry they are used for the treatment of many disorder [15]. All these phytochemicals give a strong immunity in the form of resistance against many insects and herbivores as well [16].…”
Section: Introductionmentioning
confidence: 99%